Hubungan Status Gizi terhadap Awitan Pubertas Anak Perempuan - Tiara Calista Larasati; Suganda Tanuwidjaja; Retno Ekowati (Bandung Conference Series: Medical Science, 2022)
Abstract. Puberty is a stage in the process of child growth and development because puberty is a transition period from childhood to adulthood. The age of onset of puberty varies greatly, some girls experience puberty at the age of 8 to 13 years with the average age of puberty for girls being 11 years. Changes in the onset of puberty, either too early or late, can have various impacts, including behavioral, social, emotional problems and an increased risk for the development of reproductive tract cancer, cardiometabolic disease, diabetes mellitus and breast cancer in adulthood. One of the factors related to the onset of puberty is nutritional status. The purpose of this study was to examine the relationship between nutritional status and the onset of puberty in girls. The type of research used is a literature review with a scoping review method with a data synthesis database, namely Pubmed, ScienceDirect, Springerlink and Google Schoolar. The number of articles obtained was 4,701 from 2016 to 2021. The article screening used the PRISMA method and a critical appraisal was carried out so that three suitable articles were obtained. This study resulted in factors related to the onset of puberty in girls, namely nutritional status. Based on the results of the review, there were 2 articles which showed that there was a significant relationship between BMI and age of menarche in girls. The conclusion is that there is a relationship between nutritional status and the onset of puberty in girls. Abstrak. Pubertas merupakan tahap dalam proses tumbuh kembang anak karena pubertas adalah masa transisi masa anak-anak menuju dewasa. Usia awal pubertas sangat bervariasi, sebagian anak perempuan mengalami pubertas di usia 8 sampai 13 tahun dengan usia rata-rata pubertas anak perempuan adalah 11 tahun. Perubahan awitan pubertas baik terlalu awal atau terjadi keterlambatan, dapat menimbulkan berbagai dampak, diantaranya adalah dampak perilaku,sosial,masalah emosional dan peningkatan resiko untuk perkembangan kanker saluran reproduksi, penyakit kardiometabolik, diabetes mellitus dan kanker payudara di masa dewasa. Faktor yang berkaitan dengan awitan pubertas salah satunya adalah status gizi. Tujuan penelitian ini adalah untuk melihat hubungan status gizi terhadap awitan pubertas anak perempuan. Jenis penelitian yang digunakan adalah literature review dengan metode scoping review dengan database sintesis data yaitu Pubmed, ScienceDirect, Springerlink dan Google Schoolar. Jumlah artikel yang didapatkan sebanyak 4.701 dari tahun 2016 sampai 2021, Screening aritkel menggunakan metode PRISMA dan dilakukan critical appraisal sehingga di dapatkan tiga artikel yang sesuai. Penelitian ini menghasilkan faktor yang berhubungan dengan awitan pubertas anak perempuan yaitu status gizi. Berdasarkan hasil review ditemukan 2 artikel yang menunjukkan bahwa terdapat hubungan yang signifikan antara BMI dengan usia menarche pada anak perempuan. Simpulan terdapat hubungan antara status gizi dengan awitan pubertas anak perempuan.